Super-resolution Localization and Defocused Fluorescence Microscopy on Resonantly Coupled Single-Molecule, Single-Nanorod Hybrids - Su, Liang (ACS Nano, 2016)
[Image: see text] Optical antennas made of metallic nanostructures dramatically enhance single-molecule fluorescence to boost the detection sensitivity. Moreover, emission properties detected at the optical far field are dictated by the antenna. Here we study the emission from molecule–antenna hybrids by means of super-resolution localization and defocused imaging. Whereas gold nanorods make single-crystal violet molecules in the tip’s vicinity visible in fluorescence, super-resolution localization on the enhanced molecular fluorescence reveals geometrical centers of the nanorod antenna instead. Furthermore, emission angular distributions of dyes linked to the nanorod surface resemble that of nanorods in defocused imaging. The experimental observations are consistent with numerical calculations using the finite-difference time-domain method.